2021
DOI: 10.1039/d1cc05196b
|View full text |Cite
|
Sign up to set email alerts
|

A new metal–organic framework based on rare [Zn4F4] cores for efficient separation of C2H2

Abstract: Assembly via 1,4-benzenedicarboxylate linker and Zn2+ ions afforded a new MOF containing novel [Zn4F4] cubane cores, showing excellent C2H2 separation from C2H2–CO2 and C2H2–CH4 mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…This material possesses a high coordination ligancy of bridged and terminal fluorine with metal nodes, which is very rarely reported in MOFs. 20,21,23 Hydrogen bonding could then be steadily formed between the framework and C 2 H 2 molecules, e.g. , C–H⋯F and C–H⋯O F (from furan rings), thus enhancing C 2 H 2 capture.…”
Section: Introductionmentioning
confidence: 99%
“…This material possesses a high coordination ligancy of bridged and terminal fluorine with metal nodes, which is very rarely reported in MOFs. 20,21,23 Hydrogen bonding could then be steadily formed between the framework and C 2 H 2 molecules, e.g. , C–H⋯F and C–H⋯O F (from furan rings), thus enhancing C 2 H 2 capture.…”
Section: Introductionmentioning
confidence: 99%
“…The permanent porosity of NUM-11a was assessed by N 2 adsorption at 77 K and CO 2 adsorption at 195 K. The single-component gas adsorption capacities of N 2 and CO 2 for NUM-11a ·are 11.24 and 88.70 cm 3 g –1 , respectively (Figure a). The Brunauer–Emmett–Teller (BET) surface area of NUM-11a ·was determined to be 374.2 m 2 g –1 based on the CO 2 adsorption isotherm at 195 K. Apparently, no considerable uptake amount is observed in the N 2 sorption isotherms at 77 K, probably owing to the strong host–guest interactions between the N 2 guest molecule and the channel windows, blocking N 2 diffusion into the MOF, and the low kinetic energy of N 2 . …”
Section: Resultsmentioning
confidence: 99%
“…[27][28][29] Meanwhile, we also found that μ 3 -F-bridged clusterbased MOFs have been reported using some transition metal centers, such as [M 3 (μ 3 -F)] (M = Fe, Ni, Zn, etc.). [30][31][32][33] However, a Mg-organic framework with μ 3 -F-bridged metal clusters has not been easy to obtain to date. On the other hand, the design and synthesis of a novel μ 3 -F-bridged metal-organic framework as a fluorescent thermometer is still relatively scarce.…”
mentioning
confidence: 99%
“…For the F 1s spectra, the main peak located at 685.3 eV is a typical metal fluoride bond, corresponding to the F-bridged dual-trinuclear cluster, and the peak located at 688.3 eV is consistent with the organic fluorine (the solvent HFP). 32 Furthermore, the elemental composition of SQNU-22 was determined using an energy dispersive spectrometer (EDS, Fig. S2 † As we all know, luminescent MOF materials have attracted much research interest due to their potential applications in chemosensors, thermometers, biomedical imaging, etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation